2020
DOI: 10.1002/mgg3.1311
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy management in a patient with stickler syndrome

Abstract: Background Stickler syndrome is a collagen disorder that can affect multiple organ systems. It is characterized by ocular abnormalities, hearing loss, midfacial hypoplasia, hypermobility, and joint abnormalities. The phenotypic expression of Stickler syndrome can vary among those affected. Since Stickler syndrome is a collagen disorder, it is possible to expect pregnancy complications similar to those reported in other collagen disorders. To our knowledge, there is only one case report in the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Although penetrance is high, the clinical picture outside the eye is highly variable [1]. Since Stickler syndrome is a connective tissue disease, it is thought to increase the risk of preterm premature rupture of membranes and an incompetent cervix, leading to preterm delivery [5].…”
Section: Discussionmentioning
confidence: 99%
“…Although penetrance is high, the clinical picture outside the eye is highly variable [1]. Since Stickler syndrome is a connective tissue disease, it is thought to increase the risk of preterm premature rupture of membranes and an incompetent cervix, leading to preterm delivery [5].…”
Section: Discussionmentioning
confidence: 99%
“…Prior survey studies reported that some obstetricians advocate for assisted delivery via cesarean section or instrumental delivery instead of spontaneous vaginal delivery for patients who have a history of RRD repair [2,3]. However, several studies in the literature suggest that no correlation exists between RD and labor or spontaneous vaginal delivery [4][5][6][7].…”
Section: Retinal Detachment and Childbirthmentioning
confidence: 99%